2018
DOI: 10.1536/ihj.17-467
|View full text |Cite
|
Sign up to set email alerts
|

Successful Transcatheter Diagnosis and Medical Treatment of Right Atrial Involvement in IgG4-related Disease

Abstract: IgG4-related disease (IgG4-RD) is a fibro-inflammatory disorder characterized by lymphoplasmacytic infiltration of numerous IgG4-positive plasma cells, leading to fibrous thickening in the affected tissue. Typical cardiovascular manifestations of IgG4-RD are periaortitis, coronary arteritis, and pericarditis. Rare cases of myocardial involvement in IgG4-RD have been reported, but surgical resection or open biopsy was required for the diagnosis in those cases. Here, we report a case in which percutaneous transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…We performed a literature review using the keywords “Immunoglobulin G4‐Related Disease” and “intracardiac/ cardiac mass” or “cardiac pseudotumor” in PubMed, Embase, and Scopus databases to search for relevant articles. Table 1 summarizes the 10 identified cases of IgG4‐RD with intra‐cardiac mass including the present case 10–18 . The mean age of all cases was 49.5 years (range: 27–69).…”
Section: Discussionmentioning
confidence: 99%
“…We performed a literature review using the keywords “Immunoglobulin G4‐Related Disease” and “intracardiac/ cardiac mass” or “cardiac pseudotumor” in PubMed, Embase, and Scopus databases to search for relevant articles. Table 1 summarizes the 10 identified cases of IgG4‐RD with intra‐cardiac mass including the present case 10–18 . The mean age of all cases was 49.5 years (range: 27–69).…”
Section: Discussionmentioning
confidence: 99%
“…In this issue of the Journal, Yano, et al reported a patient with right atrial mass that was diagnosed as an IgG4-related lesion. 2) In this patient, the serum IgG4 level was markedly elevated (816 mg/dL), and IgG4-positive plasma cell infiltration was proved in intra-cardiac echo (ICE)-guided percutaneous transcatheter biopsy, which made the diagnosis reasonable. Storiform fibrosis or obstructive phlebitis, which are characteristic but not exclusive histological features of IgG4-RD, were absent in the biopsied specimens; however, the presence of these findings is known to differ according to the organs examined.…”
Section: Article P1155mentioning
confidence: 71%
“…The most frequently reported cardiovascular presentations were aortitis (causing aortic aneurysms) [ 15 , 29 , 30 , 31 ] and pericarditis [ 32 , 33 , 34 , 35 , 36 , 37 ]. Subsequently, other forms of cardiovascular presentations were reported, such as valvular disease [ 18 , 38 , 39 , 40 , 41 , 42 ], heart block [ 18 , 43 ], and an involvement of heart chambers and coronary vessels with IgG4-related inflammatory pseudotumors [ 44 , 45 , 46 , 47 ]. Coronary artery involvement caused by coronary periarteritis with aneurysms and inflammatory pseudotumors surrounding and compressing the vessels [ 20 , 48 , 49 , 50 , 51 ] with subsequent stenosis or obstruction and ischemia have also been reported.…”
Section: Discussionmentioning
confidence: 99%